Dimethyl ether (DME) production pathways and deployment in Asia, the Middle East, and Africa: Technological advances, regional gaps, policy landscapes, and future prospects - Wiyono, Apri; Zuldian, Prima; Rozana, Monna; Saputro, Bayu Aji; Rahma, Qori Zulia; Nisfah, Nafisatun; Celik, Nevin (Pergamon-Elsevier Science Ltd, 2027)
Dimethyl ether (DME) has attracted attention as a clean fuel option due to its high combustion efficiency, nearly zero particulate emissions, and compatibility with existing liquefied petroleum gas (LPG) infrastructure. This review examines its production from synthesis gas in the Asia, Middle East, and Africa (AMEA) regions, where energy demand is rising, and feedstocks are diverse, including natural gas, coal, biomass, and municipal waste. Literature published from 2015 to 2025 was systematically analyzed to assess technological progress, regional adoption gaps, policy environments, and future potential across the AMEA regions. Findings reveal rapid advances in catalyst development, reactor design, and integration with renewable hydrogen and carbon capture, especially in East Asia, where industrial-scale facilities are operational. Conversely, the Middle East and Africa face constraints from insufficient infrastructure, policy fragmentation, and high production costs, despite abundant resources. Opportunities include waste-to-fuel pathways, integration with household energy systems, and regional policy coordination. This study concludes that successful deployment depends on harmonized regulations, targeted investments, and collaborative strategies to enable DME's role in supporting a sustainable and inclusive energy transition.
Keywords: Dme; Alternative Fuel; Energy Transition; Sustainable Energy; Technological Advancements